IDENTIFIKASI DAN PREVALENSI ENDOPARASIT (Gnathostoma sp.) PADA BELUT SAWAH (Monopterus albus) DENGAN UKURAN BERBEDA YANG DIKIRIM KELUAR PROVINSI KALIMANTAN SELATAN - Lukman Mugiyarto; Elrifadah Elrifadah; Mukhlisah Mukhlisah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2021)
This study aims to determine the type of endoparasitic worm Gnathostoma sp and the prevalence that infects rice field eel (Monopterus albus) with different grades. the method used is the descriptive method. Samples were taken from 3 different farm locations (Nor Aini, Banjar Regency, CV. Karya Bersama, Banjarbaru City, and Saberiannor Banjarbaru City), as many as 120 individuals with each grade (A, B, C, and D) totaling 30 individuals. Samples were examined using the microscopic method with 3 replications on each target organ, namely liver, meat, intestines, and kidneys. The results of the examination showed that Gnathostoma sp worm cysts were found, namely only in the liver, while in the intestines, flesh, and kidneys were not found. Based on the identification of Gnathostoma sp endoparasites seen from morphological characteristics, third-stage larvae (L3) in the phylum Nematoda, cylindrical body shape, transparent body color, and blackish brown, head shape resembling a light bulb, mouth, and has anus at the end of its body. Prevalence value in grade A = 40%; B= 30%; C= 40%, and D= 30%, this includes the category commonly or ordinary which describes that the parasite usually infects fish with a prevalence value range of 30-49%. It is still possible to send rice field eels outside of South Kalimantan Province, although the results of the examination of the test samples indicated the presence of the parasite infection Gnathostoma sp..